The Influence of Rising Groundwater on Slope Stability and Engineering Properties of Soil - Sapari, Nasiman; H.H, Indra Sati; M, Nordin (2008)
Infrastructural development on hilly and undulating grounds such as roads and highways often involves earthwork and construction of slope. Slope failures in tropical countries are common particularly during rainy seasons. This paper presents the findings of a field survey and laboratory model experiment on the influence of rising groundwater level towards the stability of slope and properties of soil. The study was based on slopes constructed in the campus of Universiti Teknologi Petronas supported by a laboratory experiment using a slope model with a dimension of 1m long x 0.5m width x 0.4m depth, packed with soil to represent a man-made slope of 34º. The levels of the groundwater in the laboratory model were varied to allow different level of water saturation inside the soil. The effects of the groundwater levels on the slope were examined by determining the engineering properties of the soil at various depths and observing the slope behavior. It was found that the slope was stable as long as the groundwater is lower than the toe of the slope. As the water level become higher than the toe, the moisture of the soil increased to level that can cause slope failure. Slope failure occurred when the moisture of the soil reached 40%.